Accounting Outsourcing Market in Ukraine: State and Determinants of Development - Nadiya Shkromyda; Vitalii Shkromyda; Taras Gnatiuk (Vasyl Stefanyk Precarpathian National University, 2022)
The development of information technologies over the last decade has significantly influenced approaches to business, forces companies to review management methods, and actively implement an effective policy of business process optimization. The reduction of transaction costs and the concentration of company management on their operational activities contributed to the possibility and development of ways of delegating other business processes to a third party - outsourcers. In this context, the practice of outsourcing accounting services has become widely used. Accounting outsourcing in Ukraine is borrowed from foreign experience and has widely established itself as a separate independent type of economic activity while developing various types and forms of outsourcing. It was concluded that the number of participants in the accounting outsourcing market in Ukraine is stable and gradually increasing. This testifies to the growing trust in accounting outsourcing among the representatives of the local business environment and the understanding that the delegation of accounting and reporting functions to external providers has its feasibility and advantages. Moreover, the studied market is characterized by an increase in business activity, as the number of personnel employed in outsourcing companies and the volume of implemented accounting services is gradually increasing. The indicated increase refers both to the market as a whole and the natural entities-entrepreneurs, which testifies to the positive dynamics of changes among the representatives of small and medium-sized businesses. It should be noted that the relatively young Ukrainian market of accounting outsourcing is developing successfully, has tendencies towards expansion, and is attractive to potential international investors. The theoretical value of the conducted research is the elaboration of the key determinants of the functioning of accounting outsourcing, which, we believe, have both short-term and long-term perspectives, and will contribute to the development of accounting services under outsourcing conditions.